DEPRESSION, INFLAMMATION AND CARDIOVASCULAR BURDEN IN MIDDLE AGE TWINS. (11th November 2018) - Toomey, R; Coyne, A; Franz, C; McKenzie, R; Panizzon, M; Kremen, W; Lyons, M
Abstract: Depression is a risk factor for both dementia and cardiovascular disease as people age. Some hypothesize that depression is a risk factor for dementia via its relationship with vascular burden (VB) and that this may be mediated by inflammation. We sought to further understand the relationship between depression, inflammation and VB in a sample of male Caucasian participants from the Vietnam Era Twin Study of Aging (VETSA). Inflammation was measured by blood levels of C-reactive protein. Using mixed models controlling for age and non-independence of twin pairs, we found that continuous and categorical measures of depression (Center for Epidemiologic Studies Depression Scale) at wave 1 (mean age 56) and wave 2 (mean age 62) were significantly related to wave 2 inflammation. While wave 2 mild cognitive impairment was not significantly related to inflammation, VB (vascular risk factors + vascular diseases) did significantly predict inflammation, with an increase in inflammation with each additional risk factor or disease. Using generalized estimating equations controlling for age and non-independence of twin pairs, we examined a series of models using depression status and VB as predictors of inflammation. Depression status was defined by depression history at three time points: never, past only, current and past, current only. There were main effects for both depression status and VB, as well as a significant interaction between depression status and VB. The findings lend support to the idea that depression and cardiovascular burden may influence each other via inflammation and that this relationship precedes the development of dementia.